Strontium accumulation by the terrestrial and aquatic plants affected by mining and municipal wastewaters (Elazig, Turkey) - Sasmaz, Merve; Uslu Senel, Gulsad; Obek, Erdal (Springer, 2021)
The mining and municipal wastewaters in the study area are located around Elazig, Turkey. This study investigated the translocation and accumulation of Sr into 9 terrestrial-aquatic plants from the Elazig municipal wastewater, Keban Pb-Zn and Maden Cu wastewaters. Plants and their soil samples were collected from the stream/rivers on the municipal and mining areas, and Sr values in both plant parts and their soils were analyzed by ICP-MS. The mean Sr concentrations in the soil, root and shoot of the terrestrial-aquatic plants were 101, 48.2 and 80.5 ppm, respectively (on the dried weight basis). The enrichment coefficients of root (ECR) and shoots (ECS) and translocation factors of studied plants were calculated and, then, divided into several groups as a candidate, bioaccumulator and hyperaccumulator plants according to their ECR and ECSs. These groups indicated the candidate plants:Salixsp.and Tamarix tetrandra; bioaccumulator plants:Pragmitessp.and Xanthium, and hyperaccumulator plants:Typha latifolia, Bolboscholnus ascbersusandLythnium salicariafor Sr. These results showed that both bioaccumulator and hyperaccumulator plant groups had very high ability to accumulate strontium to plant parts from their soil. Therefore, these studied plants may be helpful/useful for the rehabilitation studies of municipal and mining soils contaminated by Sr.
Keywords: Strontium; Municipal and mining soils; Accumulation; Terrestrial; aquatic plant; Phytoremediation